2013
DOI: 10.1071/is12056
|View full text |Cite
|
Sign up to set email alerts
|

The classic theory of Mexican Transition Zone revisited: the distributional congruence patterns of Passalidae (Coleoptera)

Abstract: We incorporated new data to re-evaluate the biogeographical patterns in the Mexican Transition Zone (MTZ) through the recognition of congruence in the geographic distributions of Mexican passalids (Coleoptera : Passalidae). We used three different approaches to parsimony analysis of endemicity (PAE): (1) the use of specific distribution data; (2) the application of a null model of significant co-occurrence to the specific distribution data; and (3) the use of predicted potential distributions through ecologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…As the current patterns obtained for the beetles coincide largely with those reported by Morrone () and Gutiérrez‐Velázquez et al. (), we are confident in the performance of the ENM reconstructions, and therefore in their transferences to the past. Moreover, the MOP analysis demonstrated that past scenarios mostly possess climates analogous to those in the current scenario.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As the current patterns obtained for the beetles coincide largely with those reported by Morrone () and Gutiérrez‐Velázquez et al. (), we are confident in the performance of the ENM reconstructions, and therefore in their transferences to the past. Moreover, the MOP analysis demonstrated that past scenarios mostly possess climates analogous to those in the current scenario.…”
Section: Discussionsupporting
confidence: 86%
“…However, we did not include the south‐western United States where AEs are absent for our taxon groups. We compiled a database from presence records of 55 species of beetles from 19 genera in the family Passalidae and 51 species belonging to four genera in the family Scarabaeidae ( Ateuchus , Canthon , Onthophagus and Phanaeus ; Table S1.2); groups previously studied in the MTZ (Gutiérrez‐Velázquez et al., ; Halffter, ; Marshall & Liebherr, ; Miguez‐Gutiérrez, Castillo, Márquez, & Goyenechea, ; Morrone & Márquez, ). For the mammals, we included 112 species (Table S1.3) considered to be endemic to Mexico (Ceballos & Arroyo‐Cabrales, ) and those recorded in AEs in the MTZ in previous studies (Aguado‐Bautista & Escalante, ; Escalante et al., ), excluding the insular species and those of the Baja California peninsula which are not included in the MTZ.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…), and constructed a species presence/absence binary matrix (coded as “1” if present or “0” if absent) on each cell (Appendices and ), based on the individual SDM maps for all species (hereafter “complete species matrix”). From a continental (broad) scale, this grid size could be considered a fine‐grained resolution, which allows us to connect small cells when locality data points are scattered and produce low data resolution (Gutiérrez‐Velázquez et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…, ,b; Lobo and Halffter ; Gutiérrez‐Velázquez et al. ) Halffter provided a coherent theory that explains how sets of taxa that evolved in different geographical areas (cenocrons) assembled in the transition zone. This theory developed gradually, following ideas initially formulated by Halffter in 1962, being refined and clarified in successive contributions from him and other authors.…”
Section: Introductionmentioning
confidence: 99%